A study of butanol production in a batch oscillatory baffled bioreactor - N., Masngut (2013)
As with many bioprocesses, the acetone-butanol-ethanol (ABE) fermentation faces a number of economic drawbacks when compared to the petrochemical route for butanol production. In the 1920s biobutanol was the second largest biotechnology industry, after bioethanol production. However it became difficult to compete against the petrochemical route for reasons in cluding the low product butanol concentration, because of product inhibition resu lted in low butanol productivity and due to slow fermentation and low ABE yields. These lead to uneconomical butanol recovery by the conventional method, distillation, due to the high degree of dilution. Recent interest in biobutanol as a biofuel has led to re-examination of ABE fermentation with the aim of improving solvent yield, volumetric productivity and final solvent concentration to reduce the cost of production and thereby produce biobutanol that is cost-competitive with the chemical synthesis butanol.